SURVIVOR KANKER PAYUDARA STUDI KUALITATIF TENTANG UPAYA PENDERITA KANKER PAYUDARA UNTUK MEMPERTAHANKAN KUALITAS HIDUPNYA DI RSUP H. ADAM MALIK MEDAN TAHUN 2019 - DESY DWIMENDASARI SINAGA; ERLEDIS SIMANJUNTAK; FRIDA LINA TARIGAN (LP2MTBM MAKARIOZ, 2019)
Breast Cancer is the number two cancer killer in the world after cervical cancer. The majority of breast cancer sufferers assume when diagnosed with breast cancer will end in death, but only a few breast cancer sufferers who want to fight against breast cancer he suffered, they are called breast cancer survivors. A breast cancer survivor is given to someone who has finished cancer treatment, still tries to fight cancer, and can survive up to ± 5 years after being diagnosed. The purpose of the study was to explain the efforts of breast cancer sufferers to maintain their quality of life in H. Adam Malik General Hospital Medan in 2019. This type of qualitative research is a phenomological approach and uses in-depth interview data collection methods to 7 informants. The time of the study was conducted in February 2018 - May 2019. The results of the study showed that the efforts made by breast cancer patients to maintain their quality of life were by following therapies recommended by doctors and getting closer to God the Almighty. Adherence to the therapy recommended by the doctor comes from internal factors, namely self-motivation / desire, but is influenced by external factors including: family support, knowledge, circumstances, information and experiences of others. Researchers suggested that the Health Office ordered medical oncologists to provide education about breast cancer when examining patients, so that changing people's views about breast cancer always leads to death, but it can also be cured.